Desain Kebijakan Daerah Pemilihan Dewan Perwakilan Rakyat Republik Indonesia pada Pemilu Tahun 2024 - Sutianah Sutianah; Fitriyani Yuliawati; Randi Muchariman (Jurnal Syntax Admiration, 2024)
This study aims to analyze how the policy design of the Determination of Electoral Areas of the House of Representatives of the Republic of Indonesia with the Policy Design Theory initiated by Anne Larasson and Helen Ingram. This study seeks to analyze how the Regional Policy Design of the House of Representatives of the Republic of Indonesia in the 2024 Election affects democracy in Indonesia. The research method used in this study is qualitative research that is descriptive and interpretive to explain how the policy-making system of the Electoral Region of the House of Representatives of the Republic of Indonesia affects democracy by using a critical approach. The findings of this study are that the policy design of the constituency of the House of Representatives of the Republic of Indonesia in the 2024 election is a design that contains Social Construction. This can be seen from a series of processes contained in the policy-making system said by Helen Ingram and Anne Larasson which consists of the context of society that occurred before the 2024 general election, the dynamics of framing carried out by the group through the events that occurred, the context of the problem influenced by political forces and institutional culture, and finally the dynamics of design influenced by the calculation of opportunities and risks. From a series of processes that occurred, it was obtained that the design of the constituency policy of the House of Representatives itself was a design that damaged democracy.